1997
DOI: 10.1007/s003300050267
|View full text |Cite
|
Sign up to set email alerts
|

Effective doses to members of the public from the diagnostic application of ionizing radiation in Germany

Abstract: The exposure of the German population to man-made radiation results mainly from diagnostic X-ray and nuclear medical examinations. Data are presented about the annual frequency and the average dose of the various examination types for West Germany in the years 1990-1992. According to these data a yearly average of approximately 1550 diagnostic examinations using ionizing radiation were performed per 1000 inhabitants resulting in an annual per caput effective dose of 1.9 mSv. Despite the frequent use of alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 4 publications
5
39
1
10
Order By: Relevance
“…There is not a current estimation of the annual diagnostic ionizing radiation exposure in a broad U.S. population; however, two studies of German and Norwegian populations demonstrated the mean annual effective dose per patient to range from 1.1 to 1.9 mSv, assuming between 910 and 1,550 X-ray examinations per 1,000 inhabitants (16,17). At intermediate to high doses of ionizing radiation (>100 mSv), in acute or protracted doses, scientific models and epidemiological studies demonstrate deleterious effects, including carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…There is not a current estimation of the annual diagnostic ionizing radiation exposure in a broad U.S. population; however, two studies of German and Norwegian populations demonstrated the mean annual effective dose per patient to range from 1.1 to 1.9 mSv, assuming between 910 and 1,550 X-ray examinations per 1,000 inhabitants (16,17). At intermediate to high doses of ionizing radiation (>100 mSv), in acute or protracted doses, scientific models and epidemiological studies demonstrate deleterious effects, including carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of the radiation exposure from medical imaging modalities is attributable to CT, although CT examinations represent only 4-6% of all X-ray-based imaging studies in Germany [1] and in Britain [2]. Radiation exposure, therefore, remains a predominant issue in CT.…”
Section: Introductionmentioning
confidence: 99%
“…Bei Patienten, die einer Röntgenuntersuchung zugeführt werden, ist der Anteil älterer Personen in der Regel aber relativ höher als in der Gesamtbevölkerung. Die Risikoabschätzungen mit Hilfe der effektiven Dosis führt damit in diesem Kollektiv zu einer Überschätzung des Strahlenrisikos etwa um den Faktor 2 [56]. In diesem Zusammenhang wird darauf hingewiesen, dass in keiner der heute publizierten Studien ein Anstieg von Tumorerkrankungen bei effektiven Dosen unter 100 mSv beschrieben wurde [57,58].…”
Section: Bewertung Der Strahlenexposition Bei Thoraxüber-sichtsaufnahunclassified